Effects of Block Scheduling - Veal, William R.; Schreiber, James (Education Policy Analysis Archives, 1999)
This study examined the effects of a tri-schedule on the academic achievement of students in a high school. The tri-schedule consists of traditional, 4x4 block, and hybrid schedules running at the same time in the same high school. Effectiveness of the schedules was determined from the state mandated test of basic skills in reading, language, and mathematics. Students who were in a particular schedule their freshman year were tested at the beginning of their sophomore year. A statistical ANCOVA test was performed using the schedule types as independent variables and cognitive skill index and GPA as covariates. For reading and language, there was no statistically significant difference in test results. There was a statistical difference mathematics-computation. Block mathematics is an ideal format for obtaining more credits in mathematics, but the block format does little for mathematics achievement and conceptual understanding. The results have content specific implications for schools, administrations, and school boards who are considering block scheduling adoption.